MAPT Subhaplotypes in Different Progressive Supranuclear Palsy Phenotypes - Monica Gagliardi; Radha Procopio; Alessia Felicetti; Grazia Annesi; Mariagrazia Talarico; Basilio Vescio; Aldo Quattrone; Andrea Quattrone (Biomedicines)
Background: Progressive Supranuclear Palsy (PSP) is a rare neurodegenerative disorder characterized by abnormal tau protein aggregation. The MAPT gene encodes for tau protein. The MAPT locus harbors two major haplotypes, H1 and H2, with H1 and its subhaplotypes being associated with an increased risk of PSP. Methods: In this study, we genotyped rs8070723 in a cohort of 73 PSP patients, including 47 PSP Richardson Syndrome (PSP-RS) and 27 PSP variants (vPSP), and 93 age-matched healthy controls (HC) from Southern Italy. Results: Haplotype analysis identified H1 and H2 haplotypes that conferred a risk (OR, 2.620; 95% CI, 1.399–5.140; p = 0.0035) and a protective effect (OR, 0.370; 95% CI, 0.196–0.695; p = 0.0015), respectively. In addition, we genotyped five MAPT variants (rs1467967, rs242557, rs3785883, rs2471738, and rs7521) that, together with rs8070723, defined H1 subhaplotypes. We identified 18 distinct MAPT H1 subhaplotypes, among which H1j displayed a nominally significant reduced risk of PSP (OR, 0.201; 95% CI, 0.044–0.915; p = 0.0265). Conclusions: These findings reinforce the role of MAPT genetic variation in PSP pathogenesis and highlight the potential impact of haplotype diversity on disease susceptibility.